El giro humanitario en la búsqueda de los desaparecidos en América Latina: El caso del Perú - Rivas Belloso, Jairo (2024)
In the last fifty years, a significant number of Latin American countries have faced periods of massive violations of the human rights of their respective populations, whether in dictatorial regimes, during internal armed conflicts, or in the fight against organized crime (Mexico). One of the tragic consequences of these contexts is the practice of mass disappearances of people, mainly by state agents, but also by non-state armed actors. The complaints raised by relatives of the disappeared and human rights organizations have had the effect of generating obligations for States related to the determination of the whereabouts of the disappeared. In recent years, this responsibility has led to the creation of governmental entities specialized in the search for the disappeared. Under the influence of humanitarianism, these entities do not seek to prove the crime or identify those responsible, but rather to provide answers to relatives who, for a long time, have not known the final fate of their loved ones. This article, after describing the pending task of searching for the disappeared, describes the recent humanitarian turn this task has taken in Latin America, establishing an initial balance regarding its possibilities and limitations, taking the Peruvian experience as the main reference.